2015
DOI: 10.3168/jds.2014-9294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Capsicum oleoresin on productivity and immune responses in lactating dairy cows

Abstract: This study investigated the effect of Capsicum oleoresin in granular form (CAP) on nutrient digestibility, immune responses, oxidative stress markers, blood chemistry, rumen fermentation, rumen bacterial populations, and productivity of lactating dairy cows. Eight multiparous Holstein cows, including 3 ruminally cannulated, were used in a replicated 4×4 Latin square design experiment. Experimental periods were 25 d in duration, including a 14-d adaptation and an 11-d data collection and sampling period. Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 48 publications
8
67
2
Order By: Relevance
“…Capsicum oleoresin increased proportions of lymphocytes and CD4 + T cells when it was postruminally infused (2 g/d) in dairy cows (Oh et al, 2013). Dietary supplementation of Capsicum oleoresin (250 to 1,000 mg/d) linearly increased numbers of neutrophils and eosinophils in the study by Oh et al (2015). The pro-inflammatory effects of Capsicum in these studies, however, were exhibited in dairy cows without an immune challenge.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Capsicum oleoresin increased proportions of lymphocytes and CD4 + T cells when it was postruminally infused (2 g/d) in dairy cows (Oh et al, 2013). Dietary supplementation of Capsicum oleoresin (250 to 1,000 mg/d) linearly increased numbers of neutrophils and eosinophils in the study by Oh et al (2015). The pro-inflammatory effects of Capsicum in these studies, however, were exhibited in dairy cows without an immune challenge.…”
Section: Discussionmentioning
confidence: 63%
“…In previous studies with dairy cows we observed that Capsicum had stimulatory effects on immune responses (Oh et al, 2013(Oh et al, , 2015. Capsicum oleoresin increased proportions of lymphocytes and CD4 + T cells when it was postruminally infused (2 g/d) in dairy cows (Oh et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Capsaicinoids, bioactive compounds sourced from flowering Capsicum plants, demonstrated an ability to modulate the acute-phase response in dairy cows, including in response to an intravenous lipopolysaccharide (LPS) challenge. 3,98 Furthermore, postruminal supplementation of capsaicinoids increased CD4 1 T-cell proliferation. 97 By potentially affecting both the innate and adaptive branches of the immune system, capsaicinoid supplementation may be particularly beneficial during vaccination events.…”
Section: Nutraceuticalsmentioning
confidence: 98%